"Is It Good or Bad for the Air?" Latino and Asian Pacific Islander Youth–Led Messaging and Action for Environmental Justice Through Photovoice. Issue 2 (March 2022) - Evans-Agnew, Robin A.; Postma, Julie; Dinglasan-Panlilio, Joyce; Yuwen, Weichao; Reyes, David; Denney, Sheena; Olsen, Judy
Photovoice is a powerful way to generate youth reflection and social action for health promotion. While the literature offers numerous examples of photovoice studies involving youth, they are most often engaged in taking, dialoguing, and developing phototexts, but not always in the critical next stages of planning what to do with this data, in terms of analyzing and then planning change-related strategic actions. This article describes the ways in which an intergenerational environmental justice project, as part of a larger community-based participatory research program, engaged youth through all stages of a photovoice project. Latino and Asia Pacific Islander adults recruited their own and other youth to conduct a photovoice and air sample data collection, analysis, exhibition, and evaluation activity focused on addressing indoor environmental justice threats from volatile organic chemicals. We offer lessons learned and reflect on the role of intergenerational collaboration to support youth in applying a critical lens for analyzing photovoice data and advocacy for health in their communities. We conclude with implications for photovoice practice and research.